REASON, AUTHORITY, AND THE HEALING OF DESIRE IN THE WRITINGS OF AUGUSTINE - BOONE, MARK J. (LEXINGTON Books, 2019)
In Reason, Authority, and the Healing of Desire in the Writings of Augustine, Mark Boone explains Augustine's theology of desire in a cross-section of his writings. He shows that Augustine's writings consistently teach a Platonically informed, yet distinctively Christian, theology of desire.